A method for synthesizing battery-grade high-purity lithium sulfide by a liquid phase method

Battery-grade high-purity lithium sulfide was synthesized by a liquid-phase method. This method utilizes the reaction of coordination compounds of lithium salts, alkali metal sulfides, and crown ethers, combined with antisolvent and calcination steps, to solve the problems of high impurities and difficult processing of lithium sulfide in existing technologies, and achieves the preparation of high-purity and high-yield lithium sulfide.

CN120622415BActive Publication Date: 2025-11-07ZHEJIANG UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511127108.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-13
Publication Date
2025-11-07
Estimated Expiration
2045-08-13

AI Technical Summary

Technical Problem

Existing liquid-phase methods for preparing lithium sulfide produce numerous byproducts, making subsequent processing difficult and hindering the production of high-purity, battery-grade lithium sulfide.

Method used

A liquid-phase method for synthesizing battery-grade high-purity lithium sulfide uses lithium salts and alkali metal sulfides as raw materials, introduces crown ethers as catalysts, promotes the lithium sulfide reaction by forming coordination compounds, and uses antisolvents to separate and recover crown ethers. Combined with a roasting step, organic carbon and sulfur are removed, thereby improving yield and purity.

Benefits of technology

It improves the yield and purity of lithium sulfide, solves the problems of high impurity content and difficult subsequent processing, and achieves a product purity of 99.99%, making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120622415B_ABST
    Figure CN120622415B_ABST
Patent Text Reader

Abstract

The application discloses a method for synthesizing battery-grade high-purity lithium sulfide by a liquid-phase method. The specific steps are as follows: lithium salt is dissolved in solvent X to form a lithium salt solution, anhydrous M2S and crown ether are dissolved in solvent X to form an M2S solution, the lithium salt solution is added into a reaction kettle, argon is filled to replace, the M2S solution is added into the reaction kettle, stirring is conducted, then anti-solvent Y is added into the reaction kettle, stirring is conducted to obtain a suspension system, solid crude lithium sulfide is discharged from the lower end of the reaction kettle, organic solvents are recovered by rectification to recover solvent X, anti-solvent Y and crown ether respectively, the crude lithium sulfide is vacuum dried, is placed into a rotary furnace, inert gas is introduced, and calcination is conducted to remove organic carbon and sulfur, so that battery-grade high-purity lithium sulfide products are obtained, and the crown ether is recycled and used. The crown ether is introduced to form a complex with alkali metal ions, the concentration of sulfur ions in the organic solvent is improved, the reaction rate of lithium sulfide is promoted, the formation of LiMS by-products is effectively avoided, and the yield and purity of Li2S are improved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of preparation of solid-state electrolyte lithium sulfide, and particularly relates to a method for synthesizing battery-grade high-purity lithium sulfide by a liquid-phase method. BACKGROUND

[0002] Lithium sulfide (Li2S) is not only a core raw material for synthesizing sulfide solid-state electrolyte (SSE) but also an optimal positive electrode material for lithium-sulfur batteries, and therefore, in recent years, the demand for Li2S materials in the international market has been increasing. At present, there are ball milling method, solvent method, high-temperature reduction method and direct carbon composite method for preparing Li2S materials. The high-temperature reduction method using low-price lithium sulfate as raw material has attracted widespread attention. The high-temperature reduction includes magnesium hot reduction, aluminum hot reduction and carbon hot reduction, and all of them have problems such as high impurity content, difficult subsequent treatment and low yield. The hydrogen reduction method for preparing lithium sulfide has less impurities introduced than other high-temperature reduction methods, but it is easy to form a eutectic body and has a low yield. Articles (Chem. Commun., 2022, 58, 5498-5501, ACS Appl. Mater. Interfaces 2023, 15, 1358-1366) respectively report the preparation of lithium sulfide from lithium salt and sulfide in a solution system, but there are the following problems: 1) the solubility of sodium sulfide in the ethanol system is low (0.84 mol·L -1 ), and the reaction rate with lithium salt is slow; 2) during the reaction, a side reaction occurs: Li2S + Na2S → LiNaS, forming LiNaS and other impurities mixed in the Li2S solid, which is difficult to handle, and if used as a solid-state electrolyte, it seriously affects the ionic conductivity. Further improvement of the liquid-phase complex decomposition reaction synthesis method is an urgent problem to be solved for industrial production of lithium sulfide. SUMMARY

[0003] In view of the problems of the existing complex decomposition method for preparing lithium sulfide, such as many by-products, difficult subsequent treatment, although the reaction equipment is simple and easy to industrialize, but it is difficult to obtain battery-grade lithium sulfide. The purpose of the present application is to provide a method for synthesizing battery-grade high-purity lithium sulfide by a liquid-phase method, which uses lithium salt and alkali metal sulfide as raw materials, introduces crown ether as a catalyst, uses the coordination compound formed by alkali metal ions and crown ether to release S 2- , which is beneficial to the reaction of forming lithium sulfide; and subsequent addition of dichloromethane and other antisolvents not only facilitates the separation and recovery of crown ether, but also improves the yield of lithium sulfide, solving the problems of many impurities in lithium sulfide and difficult subsequent treatment.

[0004] In order to achieve the above-mentioned purpose of the present application, the following technical solutions are adopted:

[0005] The application discloses a method for synthesizing battery-grade high-purity lithium sulfide by a liquid-phase method, and comprises the following steps: dissolving a lithium salt in a solvent X to form a solution A, dissolving an alkali metal sulfide M2S and a crown ether in the solvent X to form a solution B, adding the solution A into a reaction kettle, replacing the reaction kettle with an inert gas for 10-30 min, adding the solution B into the reaction kettle under the inert gas atmosphere, reacting at 50-100 DEG C for 2-8 h, then adding an anti-solvent Y into the reaction kettle, stirring at 20-50 DEG C for 0.5-2 h until uniform, obtaining a suspension system, discharging a solid crude lithium sulfide from the lower end of the reaction kettle, recovering the solvent X, the anti-solvent Y and the crown ether by rectifying the organic solvent, vacuum drying the crude lithium sulfide, placing the lithium sulfide into a calcination device, feeding the inert gas into the calcination device at a rate of 10-50 mL / min -1 , calcining and removing organic carbon and sulfur to obtain a battery-grade high-purity lithium sulfide product, and recycling the crown ether.

[0006] Further, the solution A is prepared by weighing the lithium salt and adding into the solvent X, stirring at 20-80 DEG C for 0.5-2 h under the protection of the inert gas.

[0007] Further, the lithium salt is one of lithium chloride, lithium nitrate, lithium sulfate, lithium bromide and lithium iodide; the solvent X is one of methyl mercaptan, ethyl mercaptan, ethanedithiol, propyl mercaptan, isobutyl mercaptan and DMSO, and the water content in the X is less than 1 ppm; and the mass ratio of the lithium salt to the solvent X is 1:5-20.

[0008] Further, the solution B is prepared by weighing the anhydrous alkali metal sulfide M2S and the crown ether, dissolving in the solvent X, and stirring at 20-80 DEG C for 0.5-2 h under the protection of the inert gas.

[0009] Further, the anhydrous alkali metal sulfide M2S is one of sodium sulfide, potassium sulfide and cesium sulfide; the crown ether is one of 18-crown-6, 15-crown-5 and 21-crown-7; and the water content in the crown ether is less than 1 ppm.

[0010] Further, the anti-solvent Y is one of dichloromethane, dichloroethane and tetrahydrofuran; and the water content in the anti-solvent Y is less than 1 ppm.

[0011] Further, the vacuum drying temperature is 30-120 DEG C; the drying time is 2-12 h; and the vacuum degree is -0.1 to -0.05 MPa.

[0012] Further, the calcination device is one of a tubular furnace and a rotary furnace.

[0013] Further, the calcination temperature is 300-700 DEG C; the calcination time is 1-8 h; and the rotary speed of the rotary furnace is 1-4 r / min -1 .

[0014] Further, the inert gas is one of nitrogen, helium and argon, and the purity of the inert gas is 99.99-99.9999%.

[0015] Compared with the existing liquid-phase preparation technology of lithium sulfide, the method has the following characteristics:

[0016] 1) In view of the low solubility of sulfide in organic alcohol solvent, the present application first introduces mercaptan solvent to improve the solubility of sulfide, thereby improving the conversion rate of the reaction; in addition, the alkali metal ion and crown ether can form a coordination ion, which realizes the effective separation of alkali metal ion and sulfur ion, adjusts the concentration of sulfur ion in the solvent, promotes the nucleation rate of lithium sulfide, effectively avoids the formation of LiMS byproduct, improves the yield of Li2S, and improves the purity of Li2S.

[0017] 2) The present application first proposes a back extraction method to reduce the solubility of Li2S in organic solvent X, realize effective separation; in the process of removing organic carbon, the rotary furnace roasting method is used, which is beneficial to the uniform heating of solid and higher removal efficiency of organic carbon.

[0018] 3) The organic solvent and crown ether used in the present application are expensive, but they can be recovered by rectification and reused to reduce the cost, and also effectively solve the environmental problem; the yield of lithium sulfide is high, the reaction product is easy to separate and purify, which is beneficial to industrialized mass production, the product yield is > 90%, and the purity is 99.99%. BRIEF DESCRIPTION OF DRAWINGS

[0019] Figure 1 XRD pattern of the product lithium sulfide in Example 1. DETAILED DESCRIPTION

[0020] The method of the present application will be described in detail below in combination with specific examples, but the protection scope of the present application is not limited to this.

[0021] Example 1

[0022] A method for synthesizing battery-grade high-purity lithium sulfide by a liquid phase method, comprising the following steps: dissolving lithium chloride in ethanedithiol (water content <1 ppm) according to a mass ratio of 1:10, stirring at 50 DEG C for 1 h under a helium (purity 99.9999%) atmosphere to form an A solution, dissolving alkali metal sulfide sodium sulfide and 18-crown-6-ether (water content <1 ppm) together in ethanedithiol, stirring at 50 DEG C for 1 h under a helium atmosphere to form a B solution, adding the A solution into a reaction kettle, replacing with helium for 20 min, adding the B solution into the reaction kettle under a helium atmosphere, reacting at 70 DEG C for 4 h, then adding an anti-solvent dichloromethane into the reaction kettle, stirring at 30 DEG C for 1 h until uniform, obtaining a suspension system, standing for 2 h, discharging solid crude lithium sulfide from the lower end of the reaction kettle, recovering ethanedithiol, dichloromethane and 18-crown-6-ether by rectification, vacuum drying the crude lithium sulfide at 70 DEG C and a vacuum degree of -0.1 MPa for 4 h, rapidly transferring the dried lithium sulfide into a rotary furnace, passing in helium at a rate of 40 mL·min -1 -1 for 10 min, reacting at 500 DEG C at a rotary rate of 2 r·min -1 -1 for 2 h, obtaining white lithium sulfide product, with a product yield of 95%. The X-ray diffraction detection result is as shown in Figure 1 , from the XRD graph, it can be seen that only the characteristic diffraction peak of lithium sulfide (corresponding to card PDF #04-004-4920) appears, and no other impurity peaks are seen; the product is analyzed by dry method particle size, D 50 =150 nm; the metal ion content in the product is analyzed by ICP-MS, as shown in Table 1, the purity of lithium sulfide reaches 99.99%, and the ion conductivity is 4.5 ms·cm -1 .

[0023] Table 1 Test results of lithium sulfide product of Example 1 by inductively coupled plasma mass spectrometer

[0024]

[0025] Example 2

[0026] According to the mass ratio of lithium nitrate and isobutyl mercaptan (water content <1 ppm) is 1:15, lithium nitrate is dissolved in isobutyl mercaptan, under argon (purity 99.9999%) atmosphere, 70 ℃ stirring 1.5 h to form A solution, alkali metal sulfide potassium sulfide and 15-crown-5 (water content <1 ppm) are dissolved in isobutyl mercaptan together, under argon atmosphere, 70 ℃ stirring 1.5 h to form B solution, A solution is added to the reaction kettle, argon is replaced for 30 min, under argon atmosphere, B solution is added to the reaction kettle, 50 ℃ reaction for 8 h, then anti-solvent dichloroethane is added to the reaction kettle, 20 ℃ stirring 2 h until uniform, a suspension system is obtained, standing for 2 h, the solid crude lithium sulfide is discharged from the lower end of the reaction kettle, the organic solvent is recovered by rectification respectively isobutyl mercaptan, dichloroethane and 15-crown-5, the crude lithium sulfide is vacuum dried at 90 ℃, vacuum degree-0.08 MPa for 2 h, then detected by X-ray diffraction, after detection, only the characteristic diffraction peak of lithium sulfide appears, no other impurity peak is found. The dried lithium sulfide is quickly transferred to a rotary furnace, argon is introduced at a rate of 10 mL·min -1 for 30 min, 550 ℃, 4r·min -1 of rotary speed for 1.5 h, white lithium sulfide product is obtained, the product yield is 94%, the purity of lithium sulfide is 99.97%, D 50 =120 nm, ionic conductivity is 2.2 ms·cm -1 .

[0027] Example 3

[0028] According to the mass ratio of lithium iodide and ethyl mercaptan (water content <1 ppm) is 1:12, lithium iodide is dissolved in ethyl mercaptan, under nitrogen (purity 99.99%) atmosphere, 80 ℃ stirring 0.5 h to form A solution, alkali metal sulfide cesium sulfide and 21-crown-7 (water content <1 ppm) are dissolved in ethyl mercaptan together, under nitrogen atmosphere, 80 ℃ stirring 0.5 h to form B solution, A solution is added to the reaction kettle, nitrogen is replaced for 30 min, under nitrogen atmosphere, B solution is added to the reaction kettle, 60 ℃ reaction for 6 h, then anti-solvent tetrahydrofuran is added to the reaction kettle, 50 ℃ stirring 0.5 h until uniform, a suspension system is obtained, standing for 2 h, the solid crude lithium sulfide is discharged from the lower end of the reaction kettle, the organic solvent is recovered by rectification respectively ethyl mercaptan, tetrahydrofuran and 21-crown-7, the crude lithium sulfide is vacuum dried at 120 ℃, vacuum degree-0.06 MPa for 2 h, then detected by X-ray diffraction, after detection, only the characteristic diffraction peak of lithium sulfide appears, no other impurity peak is found. The dried lithium sulfide is quickly transferred to a tube furnace, argon is introduced at a rate of 15 mL·min -1The white lithium sulfide product was obtained at a rate of 10 mL·min 50 = 160 nm, and the ionic conductivity was 3.6 ms·cm -1 .

[0029] Example 4

[0030] According to the mass ratio of lithium bromide and methyl mercaptan (water content <1 ppm) of 1:8, the lithium bromide was dissolved in methyl mercaptan, and A solution was formed by stirring at 75 °C for 0.5 h under an argon (purity 99.99%) atmosphere. Alkali metal sulfide sodium sulfide and 21-crown-7 (water content <1 ppm) were dissolved in methyl mercaptan together to form B solution by stirring at 75 °C for 0.5 h under an argon atmosphere. The A solution was added to the reaction kettle, and argon was replaced for 30 min. The B solution was added to the reaction kettle under an argon atmosphere, and reacted at 75 °C for 5 h. Then, antisolvent dichloroethane was added to the reaction kettle, and stirred at 45 °C for 0.5 h until uniform to obtain a suspension system. After standing for 2 h, the solid crude lithium sulfide was discharged from the lower end of the reaction kettle. The organic solvents were recovered by rectification to obtain methyl mercaptan, dichloroethane and 21-crown-7, respectively. The crude lithium sulfide was vacuum dried at 110 °C and a vacuum degree of -0.07 MPa for 2.5 h. Then, it was detected by X-ray diffraction. The detection showed that only the characteristic diffraction peak of lithium sulfide appeared, and no other impurity peaks were found. The dried lithium sulfide was quickly transferred to a rotary furnace, and argon was passed at a rate of 10 mL·min -1 The white lithium sulfide product was obtained at a rate of 10 mL·min -1 The white lithium sulfide product was obtained at a rate of 10 mL·min 50 = 160 nm, and the ionic conductivity was 3.6 ms·cm -1 .

[0031] Example 5

[0032] According to the mass ratio of lithium sulfate and propyl mercaptan (water content <1 ppm) is 1:20, lithium sulfate is dissolved in propyl mercaptan, under the atmosphere of helium (purity 99.999%), stirring at 80 ℃ for 2 h to form A solution, alkali metal sulfide potassium sulfide and 15-crown-ether-5 (water content <1 ppm) are dissolved in propyl mercaptan together, under the atmosphere of helium, stirring at 80 ℃ for 2 h to form B solution, A solution is added to the reaction kettle, and helium is replaced for 20 min, under the atmosphere of helium, B solution is added to the reaction kettle, and reacts at 65 ℃ for 6 h, then anti-solvent dichloromethane is added to the reaction kettle, and stirring is carried out at 40 ℃ for 1 h until uniform, to obtain a suspension system, and standing for 2 h, the solid crude lithium sulfide is discharged from the lower end of the reaction kettle, and the organic solvent is recovered by rectification to obtain propyl mercaptan, dichloromethane and 15-crown-ether-5 respectively, and the crude lithium sulfide is vacuum dried at 100 ℃ and a vacuum degree of-0.08 MPa for 2.5 h, then detected by X-ray diffraction, and the detection shows that only the characteristic diffraction peak of lithium sulfide appears, and no other impurity peak is found. The dried lithium sulfide is quickly transferred to a rotary furnace, helium is introduced at a rate of 25 mL·min -1 for 20 min, and reacts at 700 ℃ with a rotary speed of 4 r·min -1 for 1 h to obtain white lithium sulfide product, the product yield is 90%, the purity of lithium sulfide is 99.89%, the D 50 is 180 nm, and the ionic conductivity is 2.6 ms·cm -1 .

[0033] Example 6

[0034] According to the mass ratio of lithium chloride and DMSO (water content <1 ppm) is 1:15, lithium chloride is dissolved in DMSO, under the atmosphere of nitrogen (purity 99.99%), stirring at 70 ℃ for 2 h to form A solution, alkali metal sulfide sodium sulfide and 15-crown-ether-5 (water content <1 ppm) are dissolved in DMSO together, under the atmosphere of nitrogen, stirring at 70 ℃ for 2 h to form B solution, A solution is added to the reaction kettle, and nitrogen is replaced for 30 min, under the atmosphere of nitrogen, B solution is added to the reaction kettle, and reacts at 60 ℃ for 5 h, then anti-solvent tetrahydrofuran is added to the reaction kettle, and stirring is carried out at 35 ℃ for 1.5 h until uniform, to obtain a suspension system, and standing for 2 h, the solid crude lithium sulfide is discharged from the lower end of the reaction kettle, and the organic solvent is recovered by rectification to obtain DMSO, tetrahydrofuran and 15-crown-ether-5 respectively, and the crude lithium sulfide is vacuum dried at 90 ℃ and a vacuum degree of-0.09 MPa for 3 h, then detected by X-ray diffraction, and the detection shows that only the characteristic diffraction peak of lithium sulfide appears, and no other impurity peak is found. The dried lithium sulfide is quickly transferred to a rotary furnace, helium is introduced at a rate of 25 mL·min -1nitrogen at a rate of 40 mL·min -1 for 8 h at a rotation rate of 2 r·min 50 = 460 nm and an ionic conductivity of 1.8 ms·cm -1 .

[0035] Example 7

[0036] The lithium chloride was dissolved in ethanedithiol (water content <1 ppm) in a mass ratio of 1:10, and A solution was formed by stirring at 50°C for 1 h under a helium (purity 99.9999%) atmosphere. Sodium sulfide, an alkali metal sulfide, was dissolved in ethanedithiol, and B solution was formed by stirring at 50°C for 1 h under a helium atmosphere. The A solution was added to a reaction kettle, and the kettle was replaced with helium for 20 min. The B solution was added to the reaction kettle under a helium atmosphere, and the reaction was carried out at 70°C for 4 h. A suspension system was obtained, and the system was allowed to stand for 2 h. Sodium chloride, an M salt, was discharged from the lower end of the reaction kettle. The organic solvent was recovered by distillation to obtain crude lithium sulfide. The crude lithium sulfide was vacuum dried at 70°C and a vacuum degree of -0.1 MPa for 4 h, and then detected by X-ray diffraction. The detection showed that not only characteristic diffraction peaks of lithium sulfide appeared, but also a LiNaS impurity peak appeared. The dried lithium sulfide was quickly transferred to a rotary furnace, and helium was introduced at a rate of 40 mL·min -1 for 10 min at 500°C and reacted at a rotation rate of 2 r·min -1 for 2 h. A white lithium sulfide product was obtained, with a product yield of 92% and a lithium sulfide purity of 99.7%. D 50 = 580 nm and an ionic conductivity of 2.0 ms·cm -1 . The experimental results show that the purity and ionic conductivity of the product lithium sulfide decrease when no crown ether is introduced into the system.

[0037] Comparative Example 1

[0038] According to the mass ratio of lithium chloride and methanol (water content <1 ppm) is 1:10, lithium chloride is dissolved in methanol, under helium (purity 99.9999%) atmosphere, stirring at 50 ℃ for 1 h to form A solution, sodium sulfide is dissolved in methanol, under helium atmosphere, stirring at 50 ℃ for 1 h to form B solution, A solution is added to the reaction kettle, helium is replaced for 20 min, under helium atmosphere, B solution is added to the reaction kettle, and reaction is carried out at 70 ℃ for 4 h to obtain a suspension system, and the system is placed for 2 h, M salt sodium chloride is discharged from the lower end of the reaction kettle, the organic solvent is recovered by rectification, methanol is recovered, and crude lithium sulfide is obtained, the crude lithium sulfide is vacuum dried at 70 ℃, vacuum degree-0.1 MPa for 4 h, and then detected by X-ray diffraction, it is detected that X-ray diffraction not only appears the characteristic diffraction peak of lithium sulfide, but also appears the LiNaS impurity peak. The dried lithium sulfide is quickly transferred to a rotary furnace, helium is introduced at a rate of 40 mL·min -1 for 10 min, reaction is carried out at 500 ℃, and the rotary rate is 2 r·min -1 for 2 h to obtain white lithium sulfide product, the product yield is 92%, the purity of lithium sulfide is 99.7%, D 50 =2.3 μm, and the ionic conductivity is 0.2 ms·cm -1 . The experimental results show that the purity and ionic conductivity of the product lithium sulfide are decreased when methanol is used as the solvent.

[0039] Comparative example 2

[0040] According to the mass ratio of lithium chloride and ethanol (water content <1 ppm) is 1:10, lithium chloride is dissolved in ethanol, under helium (99.9999%) atmosphere, stirring at 50 ℃ for 1 h to form A solution, sodium sulfide is dissolved in ethanol, under helium atmosphere, stirring at 50 ℃ for 1 h to form B solution, A solution is added to the reaction kettle, helium is replaced for 20 min, under helium atmosphere, B solution is added to the reaction kettle, and reaction is carried out at 70 ℃ for 4 h to obtain a suspension system, and the system is placed for 2 h, M salt sodium chloride is discharged from the lower end of the reaction kettle, the organic solvent is recovered by rectification, ethanol is recovered, and crude lithium sulfide is obtained, the crude lithium sulfide is vacuum dried at 70 ℃, vacuum degree-0.1 MPa for 4 h, and then detected by X-ray diffraction, it is detected that X-ray diffraction not only appears the characteristic diffraction peak of lithium sulfide, but also appears the LiNaS, LiCl impurity peak. The dried lithium sulfide is quickly transferred to a rotary furnace, helium is introduced at a rate of 40 mL·min -1 for 10 min, reaction is carried out at 500 ℃, and the rotary rate is 2 r·min -1 for 2 h to obtain white lithium sulfide product, the product yield is 90%, the purity of lithium sulfide is 99.6%, D 50= 1.1 μm, ion conductivity 0.8 ms·cm -1 The experimental results show that the purity and ion conductivity of the product lithium sulfide decrease when ethanol is used as the solvent.

[0041] Comparative Example 3

[0042] According to the mass ratio of lithium chloride to isopropanol (water content <1 ppm) of 1:10, the lithium chloride was dissolved in isopropanol, and stirred at 50°C for 1 h under a helium (99.9999%) atmosphere to form solution A. The sodium sulfide was dissolved in isopropanol, and stirred at 50°C for 1 h under a helium atmosphere to form solution B. Solution A was added to a reaction kettle, and the helium was replaced for 20 min. Solution B was added to the reaction kettle under a helium atmosphere, and reacted at 70°C for 4 h. A suspension system was obtained, and was allowed to stand for 2 h. The M-salt sodium chloride was discharged from the lower end of the reaction kettle. The organic solvent was recovered by fractional distillation of isopropanol, and the crude lithium sulfide was obtained. The crude lithium sulfide was vacuum dried at 70°C and a vacuum degree of -0.1 MPa for 4 h, and then was detected by X-ray diffraction. The detection results showed that not only the characteristic diffraction peaks of lithium sulfide appeared, but also the impurity peaks of LiNaS appeared. The dried lithium sulfide was quickly transferred to a rotary furnace, and the helium was passed at a rate of 40 mL·min -1 -1 for 10 min at 500°C, and reacted at a rotation rate of 2 r·min -1 -1 for 2 h to obtain a white lithium sulfide product. The product yield was 92%, the purity of lithium sulfide was 99.7%, D 50 = 800 nm, and the ion conductivity was 0.2 ms·cm -1 The experimental results show that the purity and ion conductivity of the product lithium sulfide decrease when isopropanol is used as the solvent.

Claims

1. A method for synthesizing battery grade high purity lithium sulfide by liquid phase method, characterized in that, The method comprises the following steps: Dissolve the lithium salt in solvent X to form solution A, dissolve the alkali metal sulfide M2S and crown ether in solvent X to form solution B, add solution A into a reaction kettle, replace with inert gas for 10-30 min, add solution B into the reaction kettle under inert gas atmosphere, react at 50-100℃ for 2-8 h, then add anti-solvent Y into the reaction kettle, stir at 20-50℃ for 0.5-2 h until uniform, obtain a suspension system, discharge the solid crude lithium sulfide from the lower end of the reaction kettle, recover solvent X, anti-solvent Y and crown ether by rectification, vacuum dry the crude lithium sulfide, then place it into a calcination device, pass inert gas at a rate of 10-50 mL·min -1 -1, remove organic carbon and sulfur by calcination to obtain battery-grade high-purity lithium sulfide product, and recycle the crown ether for use. The solvent X is one of methyl mercaptan, ethyl mercaptan, ethanedithiol, propyl mercaptan, isobutyl mercaptan and DMSO. The crown ether is one of 18-crown-6, 15-crown-5 and 21-crown-7.

2. The process for synthesis of battery grade high purity lithium sulfide by liquid phase process as claimed in claim 1 wherein, The A solution preparation step is: weighing the lithium salt and adding it into the solvent X, stirring at 20-80 ℃ for 0.5-2 h under inert gas protection.

3. A process for synthesis of battery grade high purity lithium sulphide by liquid phase method as claimed in claim 2 wherein, The lithium salt is one of lithium chloride, lithium nitrate, lithium sulfate, lithium bromide and lithium iodide; the water content in the solvent X is less than 1 ppm; and the mass ratio of the lithium salt to the solvent X is 1:5-20.

4. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The B solution preparation step is: weighing the anhydrous alkali metal sulfide M2S and the crown ether, dissolving them together in the solvent X, and stirring at 20-80 ℃ for 0.5-2 h under inert gas protection. ​ 5. A method of synthesizing battery grade high purity lithium sulfide in liquid phase as claimed in claim 4 wherein, The anhydrous alkali metal sulfide M2S is one of sodium sulfide, potassium sulfide and cesium sulfide; and the water content in the crown ether is less than 1 ppm.

6. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The anti-solvent Y is one of dichloromethane, dichloroethane and tetrahydrofuran; and the water content in the anti-solvent Y is less than 1 ppm. ​ 7. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The vacuum drying temperature is 30-120 ℃; the drying time is 2-12 h; and the vacuum degree is -0.1 to -0.05 MPa. ​ 8. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The calcination device is one of a tube furnace and a rotary furnace. ​ 9. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The baking temperature is 300-700 ℃; the baking time is 1-8 h; the rotation rate of the rotary furnace is 1-4 r·min -1 . ​ 10. The process for synthesis of battery grade high purity lithium sulfide by liquid phase method as claimed in claim 1 wherein, The inert gas is one of nitrogen, helium and argon, and the purity of the inert gas is 99.99-99.9999%. ​

Citation Information

Patent Citations

  • Liquid phase precipitation method for preparing lithium sulfide and lithium sulfide

    CN115535969A

  • Synthesis method of polydimethylsilane and application of polydimethylsilane in preparation of polycarbosilane

    CN119570040A